2020
DOI: 10.1175/waf-d-19-0217.1
|View full text |Cite
|
Sign up to set email alerts
|

Subseasonal Predictions of Tropical Cyclone Occurrence and ACE in the S2S Dataset

Abstract: Probabilistic tropical cyclone (TC) occurrence, at lead times of week 1–4, in the Subseasonal to Seasonal (S2S) dataset are examined here. Forecasts are defined over 15° in latitude × 20° in longitude regions, and the prediction skill is measured using the Brier skill score with reference to climatological reference forecasts. Two types of reference forecasts are used: a seasonally constant one and a seasonally varying one, with the latter used for forecasts of anomalies from the seasonal climatology. Models f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(57 citation statements)
references
References 38 publications
(57 reference statements)
4
48
0
Order By: Relevance
“…The recurving trajectories of TCs approaching Japan and the Korean Peninsula are also predicted at a long lead (Figures 4c and 4d). The recent study of Lee et al (2020) found that some S2S models are skillful in predicting regional TCF (in every 15° × 20° grid cell) at a long lead time out to 4 weeks based on the assessment of Brier skill score. Because the definition of track density based on the method of track‐pattern‐based model (Chu et al, 2010) is different from the probability of TCF of Lee et al (2020), it is not yet clear whether our finer resolution (5° × 5°) prediction of TC density outperforms the dynamical prediction of the S2S models.…”
Section: Hybrid Model Construction and Its Prediction Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The recurving trajectories of TCs approaching Japan and the Korean Peninsula are also predicted at a long lead (Figures 4c and 4d). The recent study of Lee et al (2020) found that some S2S models are skillful in predicting regional TCF (in every 15° × 20° grid cell) at a long lead time out to 4 weeks based on the assessment of Brier skill score. Because the definition of track density based on the method of track‐pattern‐based model (Chu et al, 2010) is different from the probability of TCF of Lee et al (2020), it is not yet clear whether our finer resolution (5° × 5°) prediction of TC density outperforms the dynamical prediction of the S2S models.…”
Section: Hybrid Model Construction and Its Prediction Resultsmentioning
confidence: 99%
“…Subseasonal prediction of TC activity has been challenging, while the state-of-the-art dynamical prediction systems show skills in the probabilistic predictions of TC occurrence anomalies with positive Brier skill scores at forecast leads up to 2-4 weeks over some basins (Gregory et al, 2020;Lee et al, 2018Lee et al, , 2020. Compared to the probabilistic prediction, the deterministic cyclogenesis (for both the location and time of TC genesis) prediction at the subseasonal timescale is much more difficult (Jiang et al, 2018).…”
Section: Summary and Discussionmentioning
confidence: 99%
See 3 more Smart Citations